From Grasslands to Global Beats: A Study of Mongolian Ethnic Music Integration in Chinese Pop - Yang, Menghao (Pacific International Journal, 2024)
This study goes into the integration of Mongolian Ethnic Music into Chinese pop culture, exploring its historical roots, musical characteristics, and contemporary manifestations. Mongolian Ethnic Music, rooted in millennia of tradition and nomadic heritage, reflects the spiritual essence and cultural richness of the Mongolian people. Through an examination of ancient origins, influences of shamanism and Buddhism, and modern developments, the evolution of Mongolian music is traced, showcasing its diverse melodic, rhythmic, and tonal qualities. The classification of Mongolian music genres and styles, including the Hulunbuir, Xilingol, Ordos, and Alxa styles, highlights regional distinctions and stylistic variations. Furthermore, the study examines the integration of Mongolian Ethnic Music into Chinese pop through the works of renowned musicians such as Tengger, Han Lei, and Dege Ma, exemplifying a fusion of traditional melodies with modern sensibilities. Ulan Tuya, Qi Feng, and Yang Weiling represent contemporary artists contributing to the diversification of Chinese pop music with their unique styles. This exploration underscores the cultural significance of Mongolian Ethnic Music as a bridge between traditions, enriching the global music landscape while preserving the heritage of the Mongolian people.